Sprayable powder of hyaluronate embedded in mildly cross-linked alginate as a post-surgical tissue adhesion barrier - Oh, Se Heang; Na, Seung Yeon; Song, Kyu Sang; Lee, Jin Ho (Macromolecular research, 2013)
Hyaluronate (HA) powder was embedded in mildly cross-linked alginate (mcALG) for the preperation of the sprayable tissue adhesion barrier. The HA/mcALG powder could easily cover a peritoneal tissue defect site without spatial restriction (by air spraying) and effectively conceal the injured tissues without migration (by muco-adhesiveness of HA). It also remained at the applied area during wound healing (by HA embedding in the network structure of cross-linked ALG). The tissue adhesion prevention ability of HA/mcALG was evaluated and compared with each HA or mcALG powder through an animal study using a rat model. The HA/mcALG powder was highly effective in preventing peritoneal tissue adhesion and did not show abnormal tissue responses during wound healing. Based on these observations, the HA/mcALG powder is expected to be a good candidate for sprayable tissue adhesion barriers in clinical applications.